Waste to health: a review of waste derived materials for tissue engineering - Ahmad Zamri, Mohd Faiz Muaz; Bahru, Raihana; Amin, Rashid; Aslam Khan, Muhammad Umar; Abd Razak, Saiful Izwan; Abu Hassan, Shukur; Abdul Kadir, Mohammed Rafiq; Mat Nayan, Nadirul Hasraf (Elsevier, 2021)
This review article provides a comprehensive overview of the utilization of waste-derived materials in tissue engineering applications. Waste-derived materials that have been transformed into various bio-ceramics and natural polymer materials have exhibited outstanding biocompatibility and biodegradability in tissue engineering applications. Interestingly, using waste-derived materials could significantly contribute to environmental sustainability by reducing waste disposal. Using waste materials significantly increases source availability while minimizing the cost of manufacturing. The desirable properties and potentials of waste materials have created great opportunities for exploring their implementation in tissue engineering. Thus, this review has summarized the recent research on waste materials in terms of the current progress, limitations, and prospects for tissue engineering applications.